A visible-light active catechol–metal oxide carbonaceous polymeric material for enhanced photocatalytic activity. Issue 1 (2nd December 2016) - Karthik, P.; Vinoth, R.; Selvam, P.; Balaraman, E.; Navaneethan, M.; Hayakawa, Y.; Neppolian, B.
Abstract : Designing new materials for sustainable energy and environmental applications is one of the prime focuses in chemical science. Abstract : Designing new materials for sustainable energy and environmental applications is one of the prime focuses in chemical science. Here, an unprecedented visible-light active catechol–TiO2 carbonaceous polymer based organic–inorganic hybrid material was synthesized by a photosynthetic route. The visible light induced (>400 nm) photosynthetic polymerization of catechol led to the formation of carbonaceous polymeric deposits on the surface of TiO2 . The band gap energy of hybrids was shifted to the visible region by orbital hybridization between 3d(Ti) of TiO2 and 2p(O), π(C) of catechol. The Tauc plot clearly revealed that 1.0 wt% catechol–TiO2 carbonaceous polymer remarkably tailored the optical band gap of TiO2 from 3.1 eV to 1.9 eV. The synthesized hybrid materials were thoroughly characterized and their photocatalytic activity was evaluated towards toxic Cr(vi ) to relatively less toxic Cr(iii ) reduction under visible light irradiation (>400 nm), and solar light-driven H2 production through water splitting. Very interestingly, the hybrid material showed 5- and 10-fold enhanced activity for photocatalytic Cr(vi ) reduction and solar light-driven H2 production respectively compared with pure TiO2 . Moreover, the hybrid materials showed enhanced stability during photocatalysis. Thus, the simple photosynthetic strategy for developing light harvesting organic–inorganic hybrid materials can open up potential applications in energy and environmental remediation.